Global trends and stratified analysis of aortic aneurysm mortality: insights from the GBD 2021 study - Yang, Weiguang; Wu, Songzhe; Qi, Feng; Zhao, Linlin; Hai, Bo; Dong, Haoju; Zhang, Bufan; Gao, Ruirong; Wu, Naishi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAortic aneurysm (AA) is a serious cardiovascular disease with a high mortality rate. The aim of this study was to provide an up-to-date assessment of global AA mortality rates from 1990 to 2021, stratified by age, sex, and sociodemographic indices (SDI).MethodThis study utilized data from the Global Burden of Disease (GBD) 2021 analyzed the global burden of AA from 1990 to 2021. A stratified analysis by sex, age, and region was conducted based on the number of deaths and age-standardized death rates (ASDR). Furthermore, the ASDR trends were evaluated using age-period-cohort models and health inequality analysis methods. Existing data were also used to predict future AA mortality.ResultIn 2021, the global number of deaths due to AA increased to 153,927.20 (95% UI: 138,413.36–165,738.65), while ASDR decreased to 1.86 per 100,000 (95% UI: 1.67–2.00). The estimated annual percentage change in ASDR was −0.81 (95% CI: −0.95 to −0.66), and the average annual percentage change was −0.99 (95% CI: −1.07 to −0.90). Significant regional differences were observed, with high SDI regions experiencing a notable decrease in mortality rates, while low and low-middle SDI regions saw a substantial increase in deaths and an upward trend in mortality rates. The annual percentage change in mortality rates for those aged 55–59 years and older was positive, identifying this age group as a significant risk factor for increased AA-related mortality. At the national level, the three countries with the highest ASDR were Armenia, Montenegro, and Nauru, while the three countries with the lowest ASDR were Saudi Arabia, Tajikistan, and Afghanistan. Predictive analyses suggest that although the number of AA-related deaths is expected to continue rising, mortality rates are projected to decline.ConclusionWhile the global number of deaths from AA is anticipated to keep increasing, the ASDR is generally declining due to advances in medical care and improvements in early intervention. However, there are significant differences between countries and SDI regions. In low and low-middle SDI regions, the ASDR continues to rise, whereas in high and high-middle SDI regions, the ASDR is steadily decreasing but still remains higher than in lower SDI regions. Therefore, early screening and effective management of high-risk groups are crucial on a global scale.